2010
DOI: 10.1002/cmdc.201000029
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy in HIV‐Infected Cells to Decrease Viral Impact by Using an Alternative Delivery Method

Abstract: The ability of dendrimer 2G-[Si{O(CH(2))(2)N(Me)(2) (+)(CH(2))(2)NMe(3) (+)(I(-))(2)}](8) (NN16) to transfect a wide range of cell types, as well as the possible biomedical application in direct or indirect inhibition of HIV replication, was investigated. Cells implicated in HIV infection such as primary peripheral blood mononuclear cells (PBMC) and immortalized suspension cells (lymphocytes), primary macrophages and dendritic cells, and immortalized adherent cells (astrocytes and trophoblasts) were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 31 publications
0
53
0
Order By: Relevance
“…7% and 1.9%, respectively) (Figure 4). By comparison, in other studies, transfection efficiencies of 36% and 90% were reported with the use of a second-generation carbosilane dendrimer in primary T lymphocytes 33 and SupT1 lymphocytes, 34 respectively. The RNA alone was taken up by 9.3% of cells.…”
Section: The Oligoribonucleotide Molecule Formed Complexes With the Cmentioning
confidence: 68%
See 2 more Smart Citations
“…7% and 1.9%, respectively) (Figure 4). By comparison, in other studies, transfection efficiencies of 36% and 90% were reported with the use of a second-generation carbosilane dendrimer in primary T lymphocytes 33 and SupT1 lymphocytes, 34 respectively. The RNA alone was taken up by 9.3% of cells.…”
Section: The Oligoribonucleotide Molecule Formed Complexes With the Cmentioning
confidence: 68%
“…The slides were fixed with paraformaldehyde and incubated for 10 minutes with Fluoroshield™ with 4′,6-diamidino-2-phenylindole (DAPI) stain and then viewed and photographed under confocal microscope, ZEISS Confocal LSM 710 (Zeiss, Oberkochen, Germany). 34 …”
Section: Confocal Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…60 Nanoparticles can improve delivery of antigens to enhance the immune response and can encapsulate antigens in their core from which antigen-presenting cells (APCs) can process and present antigens to CD4 + and CD8 + T cells or facilitate B cells to generate humoral responses. [92][93][94][95] Various polymeric and lipid-based nanoparticles have been used to deliver DNA-, protein-, or peptide-based antigens in vivo, which elicit strong cellular, humoral, and mucosal immune responses. However, no effective vaccine strategy has emerged in spite of promising preliminary results.…”
Section: Nanotechnology-based Immunotherapy For Hivmentioning
confidence: 99%
“…Thus, γ-PGA nanoparticles encapsulating various antigens may have great potential as novel and efficient protein-based vaccines against HIV-1 infection. 11,27,95 Several liposome-based systems using a variety of HIV-1 antigenic peptides such as gp160, gp41, gp120, p24, tat, gag, env, and rev have been evaluated for HIV vaccine delivery, however none of them have been able to elicit a broad neutralizing antibody response. 32 …”
Section: Nanoparticles As Adjuvants In Hiv Vaccinementioning
confidence: 99%